The photocatalytic hydrogen evolution and photoreduction CO2 selective enhancement of Co3O4/Ti3+-TiO2/NiO hollow core-shell dual pn junction. (20th December 2022) - Pan, Jiaqi; Xiao, Guangsheng; Niu, Jingjing; Fu, Yueyue; Cao, Jun; Wang, Jingjing; Zheng, Yingying; Zhu, Mei; Li, Chaorong
Abstract: The potential and threshold would be the most important issues for photocatalysis, including hydrogen evolution reaction (HER) and CO2 selective photoreduction. The Co3 O4 /Ti 3+ -TiO2 /NiO hollow core-shell heterojunction is fabricated via a continuous chemical-hydrothermal-annealing-reduction method. As demonstrated, the as-prepared Co3 O4 /Ti 3+ -TiO2 /NiO hollow core-shell heterojunction exhibits remarkable photocatalytic performance enhancement than single TiO2, including H2 evolution (∼2134.63 μmol/g∙h, ∼80 folds) and CO2 photoreduction (H2 /CH4 /CO: ∼34.85/132.25/12.65 μmol/g∙h, ∼30 folds), and achieves enhanced CO2 photoreduction selectivity, which can be mainly ascribed to the synergism of Ti 3+ /Ov and dual pn junction. There, the Ti 3+ /Ov can not only increase the solar efficiency, but also decrease the threshold of H2 O*→H* and *CO→*CHO to enhance HER and CH4 selectivity, including promote H + diffusion and H2 O/CO2 /*CO absorption. All these can be supported by the density functional theory (DFT) calculation. Additionally, the formed Co3 O4 /Ti 3+ -TiO2 /NiO dual pn junction can promote the photo-generated carrier separation/transport efficiently. Furthermore, the hollow core-shell structure obtained by Cobalt 2-methylimidazole (ZIF-67) self-template can increase solar efficiency, and the NiO nanosheets and Co3 O4 nanoparticles can increase active sites. Graphical abstract: Image 1 Highlights: >Ti 3+ /Ov decreases threshold of H2 O*.→H* to enhance HER (−0.15 to 0.93 eV) >Ti 3+ /Ov decreases threshold of *CO.→*CHO to enhance CH4 selectivity (0.72–0.47 eV) >Dual pn junction can promote carrier efficiency via appropriate potential (2 folds). >Hollow 3D structure can increase interface heterojunction (∼132.11 m 2 /g).